Application of GIS technique in the studies on fish assemblages in Shatt Al-Arab River, Basrah, Iraq - Laith F. Lazem (مجلة بغداد للعلوم, 2022)
The present study has examined the spatiotemporal varieties of the demographics of the Shatt Al-Arab River fishes and their relation to some ecological components. The aim is to forecast these groups in the unexplored parts of the waterway with an emphasis on environmental indices of diversity. Three sites in the river were selected as an observation and study of these species, which lasted from March 2019 to February 2020, the study dealt with factors affecting fishes, as Water Temperature (WT), Dissolved Oxygen (DO), Potential Hydrogen Ion (pH), Salinity (Sal), and Transparency (Tra). Gill nets, cast nets, hooks, and hand nets were adopted to collecting fish. The results indicated that the fish population comprises 60 species representing 13 orders, 28 families, all species belonged to Osteichthyes except for one (Carcharhinus leucas) which belonged to Chondrichthyes. Cyprinidae is the prevalent family embraced by nine species. WT (12.1- 33.4°C) has a considerable influence on the total number of species and individuals to the north of the watercourse. However, salinity (0.9- 8.7 mg/L) was regarded as the essential impact on the composition, distribution, and abundance of species in the rest sites. Planiliza abu was the most abundant species attaining 20.21%, followed by Oreochromis aureus (16.41%), and Carassius auratus ranked (15.92%), the dominance (D3) value was 52.54%. The results of the current study showed that most of the diversity index values are considered a moderate status. On the other hand, the majority of the richness index values are viewed as semi disturbed status in all stations, while most of the values recorded of the evenness index are deemed as semi-balanced status. The application of GIS technique by using the ordinary kriging method showed high efficiency in the Shatt Al-Arab River. Therefore, this technique can be employed in environmental studies of fishes.